A facile and green synthesis of MIL-100(Fe) with high-yield and its catalytic performance. (18th October 2017) - Han, Le; Qi, Hui; Zhang, Dan; Ye, Gan; Zhou, Wei; Hou, Changmin; Xu, Wei; Sun, Yinyong
Abstract : MIL-100(Fe) with a high yield of 93% has been successfully synthesized using a facile and green method. Abstract : MIL-100(Fe) is one of the important metal–organic frameworks due to its fascinating physicochemical properties. Generally, MIL-100(Fe) was synthesized under the conditions of adding HF and solvent. Here, we report that MIL-100(Fe) can be facilely synthesized without the addition of solvent and HF. More importantly, this approach can produce MIL-100(Fe) with a high yield of 93%. Additionally, the obtained MIL-100(Fe) exhibited good catalytic performance in the acetalization of benzaldehyde with methanol. This catalyst can still maintain the initial catalytic activity after five cycles.